2011
DOI: 10.1007/s10551-011-0873-2
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Religiosity: Consequences for Consumer Activism in the United States

Abstract: religiosity, consumer behavior, boycott, ethical judgment, complaint intentions,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 53 publications
4
79
1
1
Order By: Relevance
“…Knotts et al (2000) reported that, relative to students with lower intrinsic religious commitment, high commitment students were more inclined to view questionable activities as wrong. Such a result, however, has not appeared consistently in other studies (with the exception of recent studies examining judgments concerning the appropriateness of business support of controversial issues such as same-sex marriage; Swimberghe, Flurry, and Parker, 2011;Swimberghe, Sharma, and Flurry, 2011). Clark and Dawson (1996, p. 363), for example, predicted that intrinsically religious persons would evaluate the questionable actions depicted specifically in two of three vignettes as less ethically appropriate than nonreligious persons (p. 363), but the opposite result emerged, which led to speculation that, for example, intrinsically religious persons might be undemanding of others (pp.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Knotts et al (2000) reported that, relative to students with lower intrinsic religious commitment, high commitment students were more inclined to view questionable activities as wrong. Such a result, however, has not appeared consistently in other studies (with the exception of recent studies examining judgments concerning the appropriateness of business support of controversial issues such as same-sex marriage; Swimberghe, Flurry, and Parker, 2011;Swimberghe, Sharma, and Flurry, 2011). Clark and Dawson (1996, p. 363), for example, predicted that intrinsically religious persons would evaluate the questionable actions depicted specifically in two of three vignettes as less ethically appropriate than nonreligious persons (p. 363), but the opposite result emerged, which led to speculation that, for example, intrinsically religious persons might be undemanding of others (pp.…”
Section: Discussionmentioning
confidence: 80%
“…The more that individuals interpreted corporate support for controversial social issues as inappropriate, the more likely they were to take some retaliatory action against the company (e.g., participate in a boycott; Swimberghe, Flurry, and Parker, 2011).…”
Section: Ethical Judgments and Decisions/recommended Solutionsmentioning
confidence: 99%
“…Affiliation with a specific religion and the level of the religious intensity (i.e., religiosity) in turn affect consumer behavior through related but different paths (Wilkes et al, 1986). For example, religious beliefs and religious commitment affect consumer ethical judgments and activism consistently but through empirically distinct pathways (Swimberghe et al, 2011a). Religiosity also may have a more dominant role than religion, such that "it appears that religious commitment (rather than affiliation per se) is more relevant for marketers" (Swimberghe et al, 2011b, p. 584).…”
Section: Intrinsic/extrinsic Religiosity and Consumer Behaviourmentioning
confidence: 99%
“…For example, Vitell et al (2005Vitell et al ( , 2006 investigate religiosity and consumer ethics; Jamali and Sidani (2013) look at religiosity and CSR orientation; Ramasamy et al (2010) trace the relationship between religiosity, values, and support for CSR; Kennedy and Lawton (1998) explore the link between religiousness and business ethics; and Graafland et al (2006a) look at religious belief and executives' perceptions of business dilemmas. Specific groups of stakeholders have also been studied with, for example, research conducted on the impact of managers' religion on their practice of CSR (e.g., Arslan 2001) as well as on how religion and religiosity influence consumer behavior (e.g., Cornwell et al 2005, Swimberghe et al 2011. Of particular relevance for the present study is the large-scale study by Brammer et al (2007) which draws on data gathered from 17,000 people in 20 different countries to investigate the attitudes to CSR displayed by adherents of different religions.…”
Section: Religion and Csrmentioning
confidence: 99%